2022
DOI: 10.1101/2022.11.10.22282106
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A relationship between Emotional intelligence and perceived parenting styles among undergraduate in Delhi University, India

Abstract: Introduction: Emotional Intelligence makes a major contribution and important factor in mental health. Parenting plays a pivotal role in training emotional intelligence because parents are responsible for the overall development of child. Not many studies have been done to find the association between emotional intelligence and parenting style. The objective of the study was to find the level of emotional intelligence in college students and if there is an association with perceived parenting style whether gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…It emphasizes the significance of emotional intelligence, which can be acquired over time, compared with IQ, which is inborn. Mishra and Singh (2022) undertook a cross-sectional study among college students at Delhi University, India, exploring the level of emotional intelligence and associations with parental styles and gender as a possible modifier. The survey concluded that most of the perceived parenting styles were authoritative and followed by authoritarian.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It emphasizes the significance of emotional intelligence, which can be acquired over time, compared with IQ, which is inborn. Mishra and Singh (2022) undertook a cross-sectional study among college students at Delhi University, India, exploring the level of emotional intelligence and associations with parental styles and gender as a possible modifier. The survey concluded that most of the perceived parenting styles were authoritative and followed by authoritarian.…”
Section: Literature Reviewmentioning
confidence: 99%
“…En esa línea, la inteligencia emocional influye en el hábito personal del uso de sustancias (Kun et al, 2019), además, se relaciona con el funcionamiento familiar y el desarrollo positivo (Pérez-Fuentes et al, 2019), se corresponde con mayores niveles de autoestima y menores problemas de adicción al internet (Peng et al, 2019), también, es relacionada con la motivación, la resiliencia y el rendimiento académico (Trigueros et al, 2019). Al analizar la interacción entre estilos de crianza, agresión e inteligencia emocional, diversos estudios han evidenciado que los estilos de crianza se relacionan con la inteligencia emocional (Kokkinos & Vlavianou, 2021;Mishra & Singh, 2022;Reyes-Wapano, 2021;Yadav et al, 2021), asimismo, otros estudios han mostrado que los estilos de crianza se asocia con la agresión (Anjum et al, 2019;Castañeda & Candela, 2022;Chopra & Devdutt, 2021;Cleveland & Yu, 2019;Dámaso-Flores & Serpa-Barrientos, 2022;Ordinola, 2022;Perez-Gramaje et al, 2019), también, que la agresión se correlaciona con la inteligencia emocional (Aguilar Chacón, 2022;Castro Carrasco, 2022;Cleveland & Yu, 2019;Fayaz, 2019;Guerrero Carranza & Reyes Baca, 2020;Jiménez Alvarado, 2021).…”
Section: Introductionunclassified